Developing therapeutic monoclonal antibodies (mAbs) and antibody-based products 2 - Kayser, Veysel (Henry Stewart Talks, 2022)
Biologics, Monoclonal antibodies (mAbs), Methods for characterizing monoclonal antibodies, Antibody aggregation, Accelerated stability testing, Arrhenius plot and equation, Non-Arrhenius systems, Monoclonal antibody formulation considerations, Biobetters, Preventing aggregation via mutagenesis and hyperglycosylation